A modified regimen of low-dose rituximab therapy for patients with refractory immune thrombocytopenia associated with systemic lupus erythematosus - Shuo Zhang; Nan Jiang; Li Wang; Li Zhang; Hua Chen; Mengtao Li; Xiaofeng Zeng (SAGE Publishing, 2021)
Background: Severe and refractory immune thrombocytopenia (ITP) affects the life expectancy of patients with systemic lupus erythematosus (SLE) and poses a challenge in their clinical management. This intervention study employed a small sample size to evaluate the efficacy and safety of a modified low-dose rituximab (RTX) regimen in patients with SLE-associated refractory ITP. Methods: Eight patients with severe SLE-associated refractory ITP were enrolled in this intervention study. They received an infusion of intravenous RTX (200 mg) on days 1 and 15. The dose of corticosteroids (prescribed previously) was gradually tapered, and immunosuppressants were withdrawn. Patients were followed up at 1, 3, 6, and 12 months; platelet counts, other laboratory indicators, and side effects were recorded. We used intention-to-treat analysis to calculate the response rate. Results: Seven participants (87.5%) completed the study. At 1 month, two patients (25.0%) achieved partial response (PR); the PR rate increased to 87.5% at 3 months. At 6 months, three patients (37.5%) achieved complete response (CR). However, the CR rate dropped to 25.0% at 12 months. The overall responses (ORs) were 25.0% (2/8), 87.5% (7/8), 75.0%(6/8), and 75.0%(6/8) at 1, 3, 6, and 12 months, respectively. Two patients developed a mild infusion reaction and one discontinued the study due to herpes zoster virus infection and an allergic reaction 2 weeks after the first dose of RTX. Conclusion: Modified low-dose RTX therapy (two infusions of 200 mg every 2 weeks) could be a promising new option for patients with SLE-associated refractory ITP with a satisfactory response rate.